Entrepreneurial activity in the Russian Arctic territories compared to the all-Russian situation - Tatiana P. SKUFINA; Ekaterina A. BAZHUTOVA; Vera P. SAMARINA (Northern Arctic Federal University, 2019)
The paper considers the entrepreneurial activity of the Russian Arctic territories and reveals its specificity compared to the all-Russian situation. The relevance of the scientific task is determined by the fact that ensuring economic growth and social development of the Russian Arctic is impossible without the necessary strengthening of entrepreneurial activity. The search for a mechanism for managing Arctic entrepreneurship is currently an urgent scientific task. The paper presents the authors' estimates of the entrepreneurial activity of the Russian Arctic territories compared to the all-Russian situation. The authors present the classification of the territories of the Russian Federation and the Russian Arctic by the principal business activity related to the subject of the market manifesting it. It is argued the Arctic specificity, and local conditions determine the development of entrepreneurial activity in the Arctic for such market actors as business and the state. This feature allowed us to offer and justify recommendations to stimulate entrepreneurial activity regarding the belonging of the Arctic to a classification group.